Nightly calling patterns in a Neotropical gladiator frog - Dias, Tailise Marques; Prado, Cynthia P. A. [UNESP]; Bastos, Rogerio Pereira (Springer, 2017)
In anurans, vocalization is the primary communication form and acoustic parameters are influenced by climatic conditions, but also by social contexts. We investigated calling site use and within-individual variation of acoustic parameters throughout the night in the gladiator-frog Hypsiboas goianus. We expected that large males would call closer to the water and at higher perches to avoid dehydration and maximize sound propagation. Furthermore, we tested the prediction that males would emit more aggressive calls early in the night and more advertisement calls late at night. Male size was not correlated with either distance from the water or perch height. However, as expected, males of H. goianus adopted a calling strategy that consisted of emitting more aggressive calls early in the night and more advertisement calls later in the night. Furthermore, repetition rate and interval between notes of the aggressive calls and repetition rate of the advertisement calls showed within-individual variation throughout the night that agreed with our expectations. The calling strategy of H. goianus is probably related to the establishment of calling sites early in the night and an investment in female attraction in the middle of the night when males' aggressive interactions have faded away, or due to habituation increasing the males' aggressive thresholds. This is the first study investigating within-individual patterns of acoustic parameters of calls throughout the night for anurans.
Keywords: Anura; Calling site use; Calling pattern; Intra-individual variation; Male territoriality